“Implementación de una cámara térmica para el análisis predictivo en circuitos eléctricos”. - Bermello Suárez, Stiven Adonis (2023)
This research project is based on a study which pretends incorporating the infrared thermography technique in electrical circuits in the different equipment of the electromechanical laboratory, which belongs to the Technical University of Cotopaxi Extension La Maná. These circuits and systems as any element that performs a function, are exposed to deterioration, failure, and any other type of anomaly that may cause temporary or permanent damage to any of its components. Therefore, this shows that it is vitally important to have this tool as a maintenance and inspection plan, with the purpose of guaranteeing the useful life and optimal performance of the University equipment. It is evident the importance of proposing thermography as an inspection instrument through a document that facilitates a trained technician to carry out a thermographic verification correctly and also generate a report for understanding and transmitting the obtained information in the most convenient and efficient way. Through the implementation of this infrared thermography technique in electrical circuits, the students of the electromechanical career will acquire updated learning and carry out their respective practices to evaluate the heat points in different equipment devices.